ANALISIS HAMBATAN EKSPOR PRODUK KERAJINAN DAERAH ISTIMEWA YOGYAKARTA - Farransahat, Matahari; Ma’ruf, Ahmad (Jurnal Ekonomi & Studi Pembangunan, 2006)
The research was aimed to find OUI factors and variables on technical, administrative and regulation which are barriers on handicraft exports in Daerah Istimewa Yogyakarta in 2005 based on the exporter perception about the barrier on handicraft exports. By using first hand data or primary data and analyze with the A.HP (Analytical hierarchy Process) method.In the research concludes that the factors, according to exporters preception, the regulations on labeling and product standard is the main barrier that influence exporting process on handicrafts in DIY. Following it, is the technical and administrative problem as the second barrier influencing the handicraft exports. The third barrier is other regulations that involves the export process of handicraft. It also concludes that the variables which become barriers to handicraft export in D1Y according to exporter preception is first of all, health and envoirment conservation, second is packaging procedur, third is valuing merchandise in customs office. Beside the variables mentioned there are seven other barrier variables follows and all of those variables concluded also involves in each barrier factors mention earlier.In spite of the factors and variables of handicraft export mentioned, there are still occur classical problems in the DIY handicraft industry such as the need of capital and soft loan, marketing the product, raw material supply, workers, buyers behavior and also on illegal tax that tends to high cost economy.